Outcomes of tocilizumab and sarilumab for hospitalized patients with COVID-19: retrospective study - Ashraf Mokhtar Madkour; Ashraf Abbas El Maraghy; Boles Raafat Fadly; Ragy Mamdouh Ghaly (The Egyptian Journal of Bronchology)
Abstract Introduction Tocilizumab (TZ) and sarilumab (SL), IL-6 receptor antagonists, were utilized during the pandemic, yet direct comparisons remain limited, particularly in resource-constrained settings facing drug shortages. Hypothesis This study aimed to evaluate whether TZ and SL yield comparable clinical outcomes in hospitalized patients with severe or critical COVID-19. Methods A retrospective cohort study was conducted at Ain Shams University Obour Hospital (January–December 2021) on 100 severe/critical COVID-19 patients (50 TZ, 50 SL) receiving standard care. Outcomes included mortality, length of stay, care transitions, and adverse events. Results Demographics and baseline severity were comparable between groups. TZ demonstrated significant improvement in level of care compared to SL (p = 0.001). However, in-hospital mortality (8% vs. 20%, p = 0.148), hospital stay (14.6 vs. 15.5 days, p = 0.298), ICU stay, mechanical ventilation rates and P/F ratio change at 96h showed no significant differences. Adverse events, including secondary bacterial infections, gastrointestinal tract bleeding and liver enzyme elevations showed no significant differences between TZ and SL (p =  ≥ 0.885). Conclusion TZ and SL exhibited comparable efficacy and safety in most outcomes, supporting SL as a viable alternative during TZ shortages. This study underscores the importance of context-driven therapeutic decisions in resource-limited settings.